Comparison of two TAGteach error‐correction procedures to teach beginner yoga poses to adults. Issue 1 (18th March 2019) - Ennett, Talia M.; Zonneveld, Kimberley L. M.; Thomson, Kendra M.; Vause, Tricia; Ditor, David
Abstract : Teaching with acoustical guidance involves auditory feedback (e.g., a click sound when a desired behavior occurs) as part of a multicomponent intervention known as TAGteach. TAGteach has been found to improve performance in sport, dance, surgical technique, and walking. We compared the efficacy and efficiency of the standard TAGteach error‐correction procedure and a modified TAGteach error‐correction procedure to teach 4 novice adult yoga practitioners beginner yoga poses. Both error‐correction procedures were effective for all participants; however, the relative efficiency of these error‐correction procedures was unclear. Results are discussed in terms of limitations and considerations for future research.